Internalisasi Kearifan Lokal Sunda dalam Penguatan Profil Pelajar Pancasila Melalui Gerakan Literasi di Madrasah - Aswie, Viqhi; Ruhbani Amarulloh, Reza (JENTRE, 2024)
This study aims to find out and describe the values ​​of Sundanese local wisdom that can be implemented in literacy-based learning in madrasas in the process of strengthening the Pancasila student profile. This study uses a qualitative descriptive method by analyzing the problem and then breaking it down into ideas. the preparation of this paper uses secondary data by reviewing relevant literature from scientific articles. After the data is collected, the analysis is carried out using descriptive and comparative analysis. The profile of Pancasila students is interpreted as a profile of lifelong students with the character of faith and piety to God Almighty, noble character, global diversity, cooperation, independence, critical thinking, and creative reasoning. In this regard, Sundanese local wisdom can be internalized as silih asih, silih asah, silih asuh, silih wawangi, cageur, bageur, bener, pinter and singer. These values ​​are moral values ​​that are firmly held by the Sundanese people and are relevant to strengthening the profile of Pancasila students. In its implementation, these values ​​are designed through the literacy movement by dividing its activities into 3 stages. The first stage is the habituation stage. At this stage, the inculcation of local wisdom values ​​can be divided into each day of the learning process, so in one week of learning, students can form the expected characteristics of the Pancasila student profile. In the second stage, namely the development stage through the literacy corner. The last stage is the learning stage applying learning models that focus on students.